The Effect of Standart Operating Procedures and Work Environment on Employee Productivity at PT Bahari Eka Nusantara Tanjung Priok Branch - Sendi Priyanto; Elmira Siska (Ebisnis Manajemen, 2025)
This research aims to determine the influence of Standard Operating Procedures (SOPs) and the Work Environment on Employee Productivity at PT Bahari Eka Nusantara Tanjung Priok Branch. The population in this study involves a total of 40 employees, representing all active employees in the company. The sample used in this study is also 40 employees, selected using a saturated sampling technique, meaning the entire population is used as the sample. The data collection technique is conducted by distributing questionnaires via Google Forms to ensure efficiency and accuracy. The research methods include validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests, multiple linear regression analysis, t-tests, F-tests, and the determination coefficient test. The study results show that partially, Standard Operating Procedures have a positive and significant effect on employee productivity (ttable 5.413 > tcount 2.026). Partially, the Work Environment does not have a significant effect on employee productivity (ttable 0.672 > tcount 2.026). Simultaneously, Standard Operating Procedures and the Work Environment have a positive and significant impact on employee productivity (ttable 25.085 > tcount 3.24).